Preferred Reporting items for OBservational studies in Endodontics (PROBE) guidelines: a development protocol. (1st June 2020) - Nagendrababu, V.; Duncan, H. F.; Fouad, A. F.; Kirkevang, L. L.; Parashos, P.; Pigg, M.; Væth, M.; Jayaraman, J.; Dummer, P. M. H.
Abstract: Observational studies have a significant role in establishing the prevalence and incidence of diseases in populations, as well as determining the benefits and risks associated with health‐related interventions. Observational studies principally encompass cohort, case–control, case series and cross‐sectional designs. Inadequate reporting of observational studies is likely to have a negative impact on decision‐making in day‐to‐day clinical practice; however, no reporting guidelines have been published for observational studies in Endodontics. The aim of this project is to develop reporting guidelines for authors when creating manuscripts describing observational studies in the field of Endodontology in an attempt to improve the quality of publications. The new guidelines for observational studies will be named: 'Preferred Reporting items for OBservational studies in Endodontics (PROBE)'. A steering committee was formed by the project leaders (PD, VN) to develop the guidelines through a five‐phase consensus process. The steering committee will review and adapt items from the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) statement and the Clinical and Laboratory Images in Publications (CLIP) principles, as well as identify new items that add value to Endodontics. The steering committee will create a PROBE Delphi Group (PDG), consisting of 30 members across the globe to review and refine the draft checklist items and flowchart. The items will be assessed by the PDG on a nine‐point Likert scale for relevance and inclusion. The agreed items will then be discussed by a PROBE Face‐to‐Face meeting group (PFMG) made up of 20 individuals to further refine the guidelines. After receiving feedback from the PFMG, the steering committee will pilot and finalize the guidelines. The approved PROBE guidelines will be disseminated through publication in relevant journals, and be presented at national and international conferences. The PROBE checklist and flowchart will be available and downloadable from the Preferred Reporting Items for study Designs in Endodontics (PRIDE) website: www.pride-endodonticguidelines.org . The PROBE steering committee encourages clinicians, researchers, editors and peer reviewers to provide feedback on the PROBE guidelines to inform the steering group when the guidelines are updated.